Health and safety of young people: looking beyond the 21st century (2015)
Young people (children within the ages 14 to 24) in Nigeria today are faced with a lot of safety challenges due to modernization and technological advancement. The continuous breakdown in the family system is also not helping matters. In most cases, young people are left to make their own decision on vital issues in life. The resultant effect of some of the decisions they make put them at risk and harms them. This paper explained the safety hazards of young people in Nigeria by providing insight to the problems as we look beyond the 21st century. Special attention was given to vehicular crash, recreational injuries, use of Tire arms, human attacks, physical trauma, illicit sexual practice and the use of drugs, and any substance that constitutes a grave threat to their physical and mental well-being, as well as significantly impedes the process of learning and personal development. In looking beyond the 21st century, it is important to value the rights of young people to make their own choices. But, as with any privilege, there is a responsibility which must be sustained by young people in relation to choosing a lifestyle pattern, that is consistent with the laws of the state and community norms, which involves respect for the rights of others. Safety education should therefore be introduced to young people early before they form habits that will predispose them to safety hazards.